The Shibboleth - Jacobs, John Hornor (Minneapolis Carolrhoda Lab, 2014)
As Shreve Cannon's ability to absorb the memories of others has him teetering on the edge of insanity, he returns to the custody of the state of Arkansas, this time in a mental institution, but he must collect himself and find Jack, the Twelve-Fingered Boy, if he is to stop an unspeakable evil that is stirring in Baltimore
English stories
1 2 13 17 21
NEW_ZTN_GN
Keywords: Ability -- Fiction; Bullies -- Fiction; Memory -- Fiction; Psychiatric hospitals -- Fiction; Supernatural -- Fiction